Gossip about in-group and out-group norm deviations. Issue 1 (2nd September 2022) - Imada, Hirotaka; Rullo, Marika; Hopthrow, Tim; Van de Vyver, Julie; Zagefka, Hanna
ABSTRACT: Gossip plays an essential role in our societies, and individuals gossip about others' behavior for various reasons. While previous studies have consistently demonstrated that individuals are more willing to gossip about norm deviations, existing research has understudied the potential role of the group membership of gossip target (i.e. a person who is gossiped about) and gossip recipient (a person who is gossiped to) on the tendency to instigate gossip about norm deviation. We conducted a study ( N = 1038) in which we orthogonally manipulated the group membership of a gossip target and a gossip recipient as well as types of target behavior (normative, negative norm deviation, and positive norm deviation), and tested several preregistered hypotheses regarding the willingness to gossip and gossip motivations. We found that individuals were more willing to gossip about negative and positive norm deviations compared to normative behavior regardless of the group membership of a gossip target and recipient, except when they consider gossiping about in-group negative norm deviation toward an out-group member. Gossip motivations substantially varied depending on the valence of norm deviation and the group membership.